Capturing The Evolution of Research Trends In Tax Corruption: A Bibliometric Approach - Muhamad Subhi Apriantoro; Ardila Amelia Putri; Rozi Irfan Rosyadhi (Journal of Applied Accounting and Taxation, 2024)
This study aims to understand the evolution of publications about tax corruption and its impact on tax payments in society. In preparing this research, bibliometric analysis techniques were used to explore all publications indexed in the Scopus database on tax and corruption from 1883 to 2023. The required data was then analyzed using Excel and R. Meanwhile. Visual analysis was done on keywords and quotations. Documents simultaneously using VOSviewer. The author found 950 publications that matched the specified function, subject, and criteria. This research shows an annual growth rate of 9.22%, with the most publications on taxes and corruption in 2022. The United States is the country that contributes the most publications with affiliation to The World Bank USA. Fjeldstad, OH, became the most prolific writer on taxes and corruption. The bibliometric analysis carried out was limited to Scopus data. Other national and international databases should have been taken into account in this study. This research presents a brief overview of the literature that is accessible to researchers working in economics and provides recommendations for future research.